2021
DOI: 10.7717/peerj.11465
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and transcriptome profiling provides insight into the genes and transcription factors involved in monoterpene biosynthesis of borneol chemotype of Cinnamomum camphora induced by mechanical damage

Abstract: Background The borneol chemotype of Cinnamomum camphora (BCC), a monoterpene-rich woody plant species, is the sole source prescribed by the Chinese Pharmacopoeia for the production of natural D-borneol, a major monoterpene in BCC used for millennia as a topical analgesic in China. Nevertheless, the possible gene-regulatory roles of transcription factors (TFs) in BCC’s monoterpenoid biosynthesis remained unknown. Here, a joint analysis of the transcriptome and terpenoid metabolome of BCC induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Transcription factors regulate the transcription levels of secondary metabolite synthesis pathway genes [ 32 ]. The major transcription factor families, like NAC, ERF, bHLH, MYB, MYC, WRKY, and b-ZIP, have been found and associated with responses to biotic and abiotic stress in plants [ 33 ]. To study the relationship between transcription factors using metabolite networks, 2089 transcription factors from 58 transcription factor families were obtained from an annotation file of the A. tsao-ko genome ( Supplementary Data Table S14 ).…”
Section: Resultsmentioning
confidence: 99%
“…Transcription factors regulate the transcription levels of secondary metabolite synthesis pathway genes [ 32 ]. The major transcription factor families, like NAC, ERF, bHLH, MYB, MYC, WRKY, and b-ZIP, have been found and associated with responses to biotic and abiotic stress in plants [ 33 ]. To study the relationship between transcription factors using metabolite networks, 2089 transcription factors from 58 transcription factor families were obtained from an annotation file of the A. tsao-ko genome ( Supplementary Data Table S14 ).…”
Section: Resultsmentioning
confidence: 99%
“…officinalis , verbenone and camphor known as terpene biocompounds, in the other hand WRKY is identified in all selected modules. In addition, studies on Cinnamomum camphora showed that WRKY, MYB, AP2/ERF, bZIP and bHLH are regulate borneol biosynthesis pathway genes [ 47 ]. HB-HD-ZIP also plays a crucial role in all selected modules.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, in total, 21 terpenoids were detected ( Table 1 ). Although the genes involved in terpenoid biosynthesis are widely studied in different plants [ 20 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], genes related to the synthesis of terpenoids in sacred lotus have not been studied so far. The precursors of monoterpenes and diterpenes come from the MEP pathway in plastids, while the precursors of sesquiterpenes and triterpenes come from the MVA pathway in the cytoplasm [ 34 ].…”
Section: Discussionmentioning
confidence: 99%